Low Z target switching to increase tumor endothelial cell dose enhancement during gold nanoparticle‐aided radiation therapy. Issue 1 (31st December 2015) - Berbeco, Ross I.; Detappe, Alexandre; Tsiamas, Panogiotis; Parsons, David; Yewondwossen, Mammo; Robar, James
Abstract : Purpose: Previous studies have introduced gold nanoparticles as vascular‐disrupting agents during radiation therapy. Crucial to this concept is the low energy photon content of the therapy radiation beam. The authors introduce a new mode of delivery including a linear accelerator target that can toggle between low Z and high Z targets during beam delivery. In this study, the authors examine the potential increase in tumor blood vessel endothelial cell radiation dose enhancement with the low Z target. Methods: The authors use Monte Carlo methods to simulate delivery of three different clinical photon beams: (1) a 6 MV standard (Cu/W) beam, (2) a 6 MV flattening filter free (Cu/W), and (3) a 6 MV (carbon) beam. The photon energy spectra for each scenario are generated for depths in tissue‐equivalent material: 2, 10, and 20 cm. The endothelial dose enhancement for each target and depth is calculated using a previously published analytic method. Results: It is found that the carbon target increases the proportion of low energy (<150 keV) photons at 10 cm depth to 28% from 8% for the 6 MV standard (Cu/W) beam. This nearly quadrupling of the low energy photon content incident on a gold nanoparticle results in 7.7 times the endothelial dose enhancement as a 6 MV standard (Cu/W) beam at this depth. Increased surface dose from the low Z target can be mitigated by well‐spaced beam arrangements. Conclusions: By using the fast‐switching target, one can modulate the photon beam during delivery, producing a customized photon energy spectrum for each specific situation.